2016
DOI: 10.1371/journal.pone.0159216
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy to Survive Primary Malaria Infection: An Experimental Study on Behavioural Changes in Parasitized Birds

Abstract: Avian malaria parasites (Haemosporida, Plasmodium) are of cosmopolitan distribution, and they have a significant impact on vertebrate host fitness. Experimental studies show that high parasitemia often develops during primary malaria infections. However, field studies only occasionally reveal high parasitemia in free-living birds sampled using the traditional methods of mist-netting or trapping, and light chronic infections predominate. The reason for this discrepancy between field observation and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
2
34
0
2
Order By: Relevance
“…Occasionally, the parasite may end up in tissues of the non‐host species and cause mortality (Ilgūnas et al., ). This will, however, be difficult to detect in nature because studies of wild‐caught birds usually miss those suffering from acute infections (i.e., early stage in infection with high intensity), leading to an underestimate of the potential host range of parasites (Bensch et al., ; Mukhin et al., ). In order to understand the infections in these sporadic host species, experimental infections are required (Palinauskas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, the parasite may end up in tissues of the non‐host species and cause mortality (Ilgūnas et al., ). This will, however, be difficult to detect in nature because studies of wild‐caught birds usually miss those suffering from acute infections (i.e., early stage in infection with high intensity), leading to an underestimate of the potential host range of parasites (Bensch et al., ; Mukhin et al., ). In order to understand the infections in these sporadic host species, experimental infections are required (Palinauskas et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The avian hemosporidian parasites in the genera Leucocytozoon, Plasmodium, and Hemoproteus have been used as a model system in the study of such host-parasite interactions (Atkinson & Van Riper, 1991;Hamilton & Zuk, 1982;Poulin, Marshall, & Spencer, 2000;Zuk & Borrello, 2013), yet their documented costs-and, potentially, the magnitude of selection pressure that they exert-appear to vary widely among hosts, populations, and contexts. They can have devastating impacts in naïve populations (Atkinson & Samuel, 2010), and many studies have reported negative associations with infection in endemic areas, including reductions in condition (Marzal, Bensch, Reviriego, Balbontin, & de Lope, 2008;Merino, Moreno, Sanz, & Arriero, 2000), antipredator behavior (Garcia-Longoria, Moller, Balbontin, de Lope, & Marzal, 2015;Mukhin et al, 2016), mating display behavior (Bosholn, Fecchio, Silveira, Braga, & Anciaes, 2016), survival (Asghar et al, 2015;Krams et al, 2013;Sol, Jovani, & Torres, 2003), and reproductive output (Asghar, Hasselquist, & Bensch, 2011;Knowles, Palinauskas, & Sheldon, 2010;Marzal et al, 2013;Merino et al, 2000). Other studies, however, have reported no associations-or even positive associations-with infection (Cornelius, Davis, & Altizer, 2014;Fargallo & Merino, 2004;Piersma & van der Velde, 2012;Podmokla et al, 2014;Zylberberg et al, 2015), or have reported effects that vary among host species (Atkinson & Van Riper, 1991;Ellis, Kunkel, & Ricklefs, 2014;Sorci, 2013), host population (Piersma & van der Velde, 2012), parasite species (Asghar et al, 2011;Lachish, Knowles, Alves, Wood, & Sheldon, 2011;Marzal et al, 2008), and characteristics of individual hosts…”
Section: Introductionmentioning
confidence: 99%
“…Some of them are considered as a genetic reservoir for many threatened species (WAZA, 2005). Captive environment also offers some specials conditions to animals when compared to wildlife, such as enough food available through the year and for all individuals, protection against predators and veterinary care (Mukhin et al, 2016). On the other hand, when in captivity, animals may live in a highly populated space, which can favour the transmission of infectious diseases and parasites.…”
Section: Introductionmentioning
confidence: 99%